Hume's morality feeling and fabrication - Cohon, Rachel, 1954- (Oxford : Oxford University Press, 2008)
Rachel Cohon offers an original interpretation of the ethical thinking of the 18th-century philosopher David Hume. She focuses on two claims: that human beings figure out what is good or evil by using our feelings or emotions, and that some of the good traits we recognize are produced by informal social agreement and teaching.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hume, David, -- 1711-1776 -- Ethics; Ethics